Consumer Behaviour : A European Perspective - Solomon, Michael R.; Hogg, Margaret K.; Askegaard, Soren; Bamossy, Gary (Pearson International Content, 2019)
Now in its seventh edition, Consumer Behaviour: A European Perspective provides the most comprehensive, lively and engaging introduction to the behaviour of consumers in Europe and around the world.   The new slimline edition has 13 chapters, maintaining its breadth of coverage and making it ideal for second- and third-year undergraduates as well as Master's students. The book links consumer behaviour theory with the real-life problems faced by practitioners in many ways:  Marketing opportunity, Marketing pitfalls and Multicultural dimensions boxes throughout the text illustrate the impact consumer behaviour has on marketing activities. Consumer behaviour as I see it boxes feature marketing academics talking about the relevance of consumer behaviour issues to their everyday work. Brand new Case studies about European companies and topics give deep insights into the world of consumer behaviour. New coverage of sustainable consumption, emerging technologies, social media and online behaviour is woven throughout this edition. Online materials including multiple-choice questions and links to useful websites are available on the book's website at www.pearsoned.co.uk/solomon